Mayo registry for telemetry efficacy in arrest (MR TEA) study: An assessment of the effect of admission diagnosis on outcomes from in-hospital cardiopulmonary arrest. (2nd October 2015) - Snipelisky, David; Ray, Jordan; Matcha, Gautam; Roy, Archana; Clark, Brooke; Dumitrascu, Adrian; Bosworth, Veronica; Whitman, Anastasia; Lewis, Patricia; Vadeboncoeur, Tyler; Kusumoto, Fred; Burton, M. Caroline
Abstract : Introduction: Little data exists evaluating how different risk factors influence outcomes following in-hospital arrests. Methods: A retrospective review of patients that suffered a cardiopulmonary arrest between 1 May 2008 and 30 June 2014 was performed. Patients were stratified into subsets based on cardiac versus non-cardiac reasons for admission. Results: 199 patients met inclusion criteria, of which 138 (69.3%) had a non-cardiac reason for admission and 61 (30.7%) a cardiac etiology. No difference in demographics and non-cardiac comorbidities were present. Cardiac-related comorbidities were more prevalent in the cardiac etiology subset. Arrests with a shockable rhythm were more common in the cardiac group ( P < 0.0001), yet return of spontaneous circulation from the index event was similar ( P = 0.254). More patients in the cardiac group were alive at 24-h post resuscitation ( n = 34, 55.7% versus n = 49, 35.5%; P = 0.0085), discharge ( n = 21, 34.4% versus n = 19, 13.8%; P = 0.0018), and at last follow-up ( n = 13, 21.3% versus n = 14, 10.1%; P = 0.0434). Conclusion: Although patients with cardiac and non-cardiac etiologies for admission have similar rates of return of spontaneous circulation, those with cardiac etiologies are more likely to survive to hospital discharge and outpatient follow-up.